2009
DOI: 10.1111/j.1745-6924.2009.01125.x
|View full text |Cite
|
Sign up to set email alerts
|

Puzzlingly High Correlations in fMRI Studies of Emotion, Personality, and Social Cognition

Abstract: Functional magnetic resonance imaging (fMRI) studiesofemotion, personality, and social cognition have drawn much attention in recent years, with high-profile studies frequently reporting extremely high (e.g., >.8) correlations between brain activation and personality measures. We show that these correlations are higher than should be expected given the (evidently limited) reliability of both fMRI and personality measures. The high correlations are all the more puzzling because method sections rarely contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
1,037
2
19

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,322 publications
(1,087 citation statements)
references
References 38 publications
(50 reference statements)
8
1,037
2
19
Order By: Relevance
“…Vul, Harris, Winkielman, and Pashler (2009) found that about 40% of functional magnetic resonance imaging (fMRI) researchers reported results in their articles only for the voxel most correlated with a variable of interest (within a region of interest). This example satisfies all three conditions.…”
Section: Exceptionsmentioning
confidence: 99%
“…Vul, Harris, Winkielman, and Pashler (2009) found that about 40% of functional magnetic resonance imaging (fMRI) researchers reported results in their articles only for the voxel most correlated with a variable of interest (within a region of interest). This example satisfies all three conditions.…”
Section: Exceptionsmentioning
confidence: 99%
“…Over a decade later, and one "Voodoo correlations" (Vul et al, 2009) imbroglio and postmortem ichthyological fMRI study (Bennett et al, 2011) later, it seems everyone agrees that (a) correcting inferences for the search over the brain is essential and (b) such corrections are not consistently utilized in fMRI. Hopefully some historical perspective can strengthen the discipline's resolve to uphold good statistical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Conditions were compared using traditional t-tests implemented in SPM. Due to recent concerns (see Vul et al (2009)), displayed effect sizes were calculated by averaging extracted beta values over all voxels within a ROI.…”
Section: Statistical Analysesmentioning
confidence: 99%